2023
DOI: 10.1088/1367-2630/acfc5e
|View full text |Cite
|
Sign up to set email alerts
|

Description of bandgaps opening in chiral phononic crystals by analogy with Thomson scattering

Wei Ding,
Tianning Chen,
Chen Chen
et al.

Abstract: Chiral phononic crystals provide unique properties not offered by conventional metamaterial based on classic Bragg scattering and local resonance. However, it is insufficient to only consider the inertial amplification effect to describe its bandgap mechanism due to the absence of the bandgap caused by the chirality in some specific chiral structures. Here, we theoretically and experimentally introduce an analogy with Thomson scattering in electromagnetic waves to characterize the bandgap phenomena in chiral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…for this bandgap formation. This indirectly demonstrates that the analogous Thomson scattering [58] has universality.…”
Section: (A)mentioning
confidence: 68%
See 4 more Smart Citations
“…for this bandgap formation. This indirectly demonstrates that the analogous Thomson scattering [58] has universality.…”
Section: (A)mentioning
confidence: 68%
“…According to the conditions of elastic Thomson scattering [58], ISL and SYL have to own translationrotation coupling. It has been demonstrated that the chirality is an effective way to achieve the motioncoupling condition, thus producing the inertial amplification effect [59,61].…”
Section: / 26mentioning
confidence: 99%
See 3 more Smart Citations